Measurement of flow harmonics with multi-particle cumulants in Pb+Pb collisions at √sNN = 2.76 TeV with the ATLAS detector - Aad, G. (2014)
ATLAS measurements of the azimuthal anisotropy in lead?lead collisions at s NN = 2.76 TeV areshown using a dataset of approximately 7 μb −1 collected at the LHC in 2010. The measurements areperformed for charged particles with transverse momenta 0.5 < p T < 20 GeV and in the pseudorapidityrange |η| < 2.5. The anisotropy is characterized by the Fourier coefficients, v n , of the charged-particleazimuthal angle distribution for n = 2?4. The Fourier coefficients are evaluated using multi-particlecumulants calculated with the generating function method. Results on the transverse momentum,pseudorapidity and centrality dependence of the v n coefficients are presented. The elliptic flow, v 2 ,is obtained from the two-, four-, six- and eight-particle cumulants while higher-order coefficients, v 3and v 4 , are determined with two- and four-particle cumulants. Flow harmonics v n measured with four-particle cumulants are significantly reduced compared to the measurement involving two-particle cu-mulants. A comparison to v n measurements obtained using different analysis methods and previouslyreported by the LHC experiments is also shown. Results of measurements of flow fluctuations evalu-ated with multi-particle cumulants are shown as a function of transverse momentum and the collisioncentrality. Models of the initial spatial geometry and its fluctuations fail to describe the flow fluctuationsmeasurements.